Sultan Qaboos University Students' Attitudes towards Inclusion of Their Peers with Disabilities - Ibrahim Al Qaryouti; Jokha Al Shukaili (Sultan Qaboos University, 2015)
The present study aimed to identify attitudes of students of Sultan Qaboos University towards the inclusion of disabled peers. To achieve the objective of the study, the researchers used a scale to measure students' attitudes towards inclusion. The final version of the scale consisted of 34 items after verification of validity and reliability. The results showed no significant difference between students of colleges of science and humanities in their attitudes towards the inclusion of their disabled peers. However, there were statistically significant differences in attitudes towards the inclusion of students with disabilities in terms of gender; in favor of females domain and the total score. There were differences in attitudes towards the inclusion of students with disabilities among males and females in the college of science, and in favor of females on all domains of the scale. Also, there was significant interaction effect (gender by academic level). Meanwhile, the results of the study did not show statistically significant differences in attitudes between male and female students in the College of Humanities The exception was in behavioral domain, where female students' attitudes were more positive towards inclusion than male students. In light of these results, the study recommended to study the attitudes of both administration and academic staff towards the inclusion of students with disabilities in Sultan Qaboos University.